2015
DOI: 10.1128/aem.02616-14
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity and Virulence Profiles of Historical Escherichia coli O157 Strains Isolated from Clinical and Environmental Sources

Abstract: c Escherichia coli O157:H7 is, to date, the major E. coli serotype causing food-borne human disease worldwide. Strains of O157 with other H antigens also have been recovered. We analyzed a collection of historic O157 strains (n ‫؍‬ 400) isolated in the late 1980s to early 1990s in the United States. Strains were predominantly serotype O157:H7 (55%), and various O157:non-H7 (41%) serotypes were not previously reported regarding their pathogenic potential. Although lacking Shiga toxin (stx) and eae genes, seroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The mechanisms underlying the evolution and emergence of such new bacterial pathogens are not well understood, and these atypical strains now are attracting more attention. The variety of virulence determinants due to horizontal gene transfers of mobile elements, such as pathogenicity islands (PAIs), phages and plasmids contributing to a strain's pathogenic potential [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the evolution and emergence of such new bacterial pathogens are not well understood, and these atypical strains now are attracting more attention. The variety of virulence determinants due to horizontal gene transfers of mobile elements, such as pathogenicity islands (PAIs), phages and plasmids contributing to a strain's pathogenic potential [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, T22 also shows the non-sorbitol-fermenting (NSF) phenotype (Tóth et al, 2009). In a more recent study, conducted with 400 O157 strains including nine of the O157:H43 strains, pulsed field gel electrophoresis (PFGE) patterns suggested that the O157 serogroup became divergent according to the different H types (Rump et al, 2015). Out of the nine O157:H43 strains investigated by Rump et al, (2015) only two were NSF, and one of theme lacked all EHECspecific marker genes.…”
Section: Phylogenetic Relationsmentioning
confidence: 99%
“…Similarly, none of the 13 EHEC-specific marker genes are present in the genome of T22. Because the study was limited to these 13 genes, no further genetic comparison is possible at present between T22 and the O157:H43 strains investigated by Rump et al (2015).…”
Section: Phylogenetic Relationsmentioning
confidence: 99%
“…In 1982, the first Shiga toxin-producing Escherichia coli (STEC) serotype, E. coli O157:H7, was associated with mild to severe human disease and outbreaks ( 1 ). Since then, its diversity has been widely studied ( 2 ). However, not only O157:H7 has been implicated with human diseases, as >400 STEC serotypes have also been found to be responsible for them ( 3 ).…”
Section: Genome Announcementmentioning
confidence: 99%